Penggunaan Kaidah Rasm Surat Yasin dalam Naskah Mushaf al-Qur’an Koleksi Pondok Pesantren Tebuireng - Adrika Fithrotul Aini (Studia Quranika, 2020)
This research explains the characteristic model of rasm in copying Mushaf al-Qur'an Pesantren Tebuireng collection. The object of this research is Surat Yasin. This Research will try to see the use of rasm in copying based on the rules described by Imam al-Suyuti in his temple al-Itqan. This study concluded that the copying of the Mushaf al-Qur'an collection of Pondok Tebuireng used Imla'i form in hazf rules or remove letters. However, in other rules, the rule of rasm usmani part ziyadah, hamz, badl, al-Fasl wa al-Wasl, and qiraat were using the form of a rasm usmani.